Spectral study on the interaction of ciliate Euplotes octocarinatus centrin and metal ions - Wang, Zhi-Jun; Zhao, Ya-Qin; Ren, Lie-Xiang; Li, Guo-Ting; Liang, Ai-Hua; Yang, Bin-Sheng (Journal of photochemistry and photobiology. A, Chemistry., 2007)
Centrin is a low molecular mass (20 kDa) protein that belongs to the EF-hand superfamily of calcium-binding proteins. Centrin and calmodulin apparently function in distinct calcium signaling pathways despite substantial sequence similarity. To understand how centrin function, the glycine in position 115, the sixth amino acid of the loop of the protein's third EF-hand, was converted into tryptophan (Trp). Local and overall changes were monitored for interactions between cations and Euplotes centrin and the mutant using fluorescence and UV spectroscopies. The results show that the binding of four Ca 2+ ions to centrin with two higher affinity (sites III and IV) and two lower affinity (sites I and II), and the relative affinity of site IV is higher than that of site III. The secondary structure change of centrin and the mutant resulting from metal ions binding was measured by CD spectra. Centrin undergo a conformation change induced by Ca 2+ binding from “closed” to “open”, through 2- p-toluidinylnaphthalene-6-sulfonate (TNS) as a probe, the different contributions to conformation change from the different sites were investigated, providing some insights into the molecular mechanism of centrin functions in the cell.